Reduction Of Heavy Metals Sludge By Vermicomposting Technique - Hamdi, Shaymaa Mundher Ahmed (2011)
Two kinds of treatments were used in the current thesis, namely, biological and chemical treatments, to reduce the concentration of four heavy metals (Al, Ni, Zn, and Pb) in the sludge collected from the electronic industry. A biological treatment called vermicomposting technique was employed to expose four different ratios of sludge (20, 50, 80, and 100%) mixed with goat manure and rice straw as a composting material to the earthworm species Eisenia fetida for four weeks. The metal concentration exhibited a significant decrease with an increase in time.